PENGARUH PENERAPAN TEKNIK OPERAN KERTAS IDE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 LENGAYANG - Retni, Retni; Mukhni, Mukhni; Edriati, Sofia (STKIP PGRI Sumbar, 2013)
The background of this research is the students easy forget with concept that cannot give opinions and ideas. The purpose of this research such as, (1) to know how development students understanding of Mathematis concept, (2) to know what students understanding of Mathematis concept that use operan kertas ide technique is more good than students understanding of Mathematis concept by using conventional learning at class of VIII SMPN 3 Lengayang. This research is experiment research with random design toward subject. The population in this research is all of student at class of VIII SMPN 3 Lengayang of year 2013/2014. Technique of sampling is done by random sampling, furthermore it is chosen VIII.3 class as experiment class and VIII.4 class as control class. Instrument of this research is quiz and final test that is formed valid and reliable test in 0,83. Based the data analysis is knew that both of classes is normal distribution and homogeny in real taraf . Hyphotesis test result is got p-value Â which is more little than , so hyphotesis is accept. In conclusion that students understanding of Mathematis concept is applay by using convensional learning at class of VIII SMPN 3 Lengayang.